Effect of Seed Size and Osmo-Priming on Yield and its Component Characters in Indian Mustard (Brassica nigra L.) - RAJ KUMAR; H PRASHANTH BABU (Seed Research, 2026)
Rapeseed mustard is a major oilseed crop of India. Rapid seedling establishment is an important requirement for successful crop production. Seedling establishment and speed of emergence influence the time required for seedling to reach the autotrophic phase. The present investigation showed that, influence of seed size differed significantly for two traits viz No. of secondary branches and days to 50% flowering and it was non-significant for other traits. The effect of priming treatments differed significantly for five traits; viz days to flowering, days to 50% flowering, No. of primary branches, No. of secondary branches and seed yield per plant; whereas, it was non-significant for other yield attributing traits. Hydro priming had a prominent effect on most of the characters and is a preferable method for improving seed yield. This was followed by KCI treatment, which showed its positive effect on yield related traits like number of seeds per pod and 100 seed weight. The NaCl treatment has good effect in increasing primary branches and reducing number of days required to flowering. Bold seed showed higher number of secondary branches, 100 seed weight and took more number of days to first flowering and 50% days to flowering. Medium sized seeds gave better mean performance for most of the traits under consideration and this was followed by small size seed. All the traits showed positive correlation with yield and were non-significant, indicating that Bold/large seed size and seed priming produces more seed weight.